Nostalgia and the ‘New Visibility’ of Religion - Christopher Deacy (Religions, 2020)
This article examines the role that religion plays in a sample of the lives and career journeys of eight academic staff or alumni at a British university. Using the ‘Nostalgia Interviews with Chris Deacy’ podcast as source material, the aim is to look at the intersection between traditional and implicit conceptualisations of religion, that arise in the course of interviews that the author has undertaken, with a view to shedding light on what this says about the role that religion plays when people reminisce about their past, how this relates to contemporary religious experience for them, and whether this might be identified as an example of the ‘new visibility’ of religion. It will conclude that the way we understand the location and parameters of religion in the contemporary world needs to be re-orientated and re-framed, in the light of the presence of those less formal and structured forms of religion, which often overlap with formal religious practices, but are often articulated without reference to it.